P-310 The last journey: 448KHz electrostimulation and its effects on the endometrium of women going through menopause. (30th June 2022) - Irollo, A.M; Bracone, G; Renzi, A; Gangale, M.F; Tartaglia, M.L; Calabrese, G; Irollo, A.M; Criscuolo, C; Tavoletta, B; Pellegrini, M; Ghelardi, C; De Simone, M; et al.
Abstract: Study question: Could 448KHz electrostimulation be beneficial in the endometrial preparation for transfer in pre-menopausal or menopausal women? Summary answer: Few women had adequate endometrium (8.3%) with standard treatments, which increased to 54.1% when combined with aspirin-sildenafyl, while when combined with 448KHz is over 75% What is known already: We know that electrical stimulation is used in tissue engineering as a new regenerative medicine approach, which promotes cell proliferation and differentiation. In addition, it improves cell membrane permeability and cell metabolism. Study design, size, duration: In the retrospective clinical study a total of 96 patients were considered, all in premenopausal or menopausal state, with inadequate endometrial response to common therapies and failure to transfer. In the following cycle, attempts were made to optimize the level of endometrial preparation by various approaches. Participants/materials, setting, methods: The instrument used for electrostimulation was INDIBA. The 96 patients were divided into 4 groups: group A received estrogen therapy and 448KHz electrostimulation, group B received estrogen therapy, group C received estrogen therapy, aspirin and sildenafyl support, group D received estrogen therapy, aspirin-sildenafyl support and 448KHz electrostimulation. Main results and the role of chance: Electrostimulation was found to be beneficial in group A (with electro-stimulation) where 75% of patients had an endometrium suitable for transfer compared to group B (without electro-stimulation) with only 8.3%. Similarly, group C (without electro-stimulation) had 54.1% of patients with a suitable endometrium, while group D (with electro-stimulation) had 87.5%. Limitations, reasons for caution: The limitations are related to the nature of the study, which is retrospective, so although the starting conditions were evaluated to reduce bias, we suggest confirmation with a prospective randomized clinical trial to validate these data, which will be our next objective. Wider implications of the findings: The common therapeutic approach of endometrial preparation, when combined with electrostimulation, leads to a drastic decrease in cancelled cycles due to an inadequate endometrium. Trial registration number: not applicable